Fine‐tuning the assessment of large‐scale temporal trends in biodiversity using the example of British breeding birds. Issue 1 (17th December 2012) - Studeny, Angelika C.; Buckland, Stephen T.; Harrison, Philip J.; Illian, Janine B.; Magurran, Anne E.; Newson, Stuart E.; Elphick, Chris
Summary The current headline indicator for ecosystem health and sustainability incorporates a geometric mean of relative abundances of breeding birds. Recently, a family of diversity measures (λ‐measures) has been proposed as a novel instrument to separate diversity trends in dominant and rare species. This makes them an ecologically informative complement to current composite diversity indices. Using both a geometric mean and the set of λ‐measures, we study habitat‐specific temporal trends in the diversity of British breeding birds. The analysis employs abundance estimates corrected for variation in detectability between individuals from different species to reduce bias. Applying generalized additive models, we predict long‐term trends. We locate significant changes in these diversity trends. While the geometric mean reveals overall diversity trends by habitat type, supplementing these by the λ‐measures provides a more nuanced picture of trends: a positive trend in the geometric mean may hide predominantly declining trends among the rarer species, which is then revealed by trends in the λ‐measures. Synthesis and Applications. Bird populations are seen as useful indicators of the health of wildlife and the countryside because they occupy a range of habitats, they tend to be towards the top of the food chain, and data is provided by long‐term surveys. Hence, many countries apply wild bird indicators (WBIs), quantifying trends in biodiversity, to monitor environmental health. The UK's WBI, for example, has become one of the government's headline indicators of sustainable development. Understanding the population changes underlying the estimated trends is indispensable if we are to allocate limited resources more effectively. Employing a novel set of measures alongside the traditional geometric mean index, we analyse diversity trends among British breeding birds. It reveals that species that are scarce, but not yet in the focus of conservation action, may be the 'losers' in biodiversity action plans. This suggests that additional resources should be devoted to species showing long‐term decline before they reach the low population levels that currently trigger large‐scale species‐specific rescue projects.